2021
DOI: 10.1016/j.amjsurg.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary contusions in patients with rib fractures: The need to better classify a common injury

Abstract: Background: Pulmonary contusions are common injuries. Computed tomography reveals vast contused lung volume spectrum, yet pulmonary contusions are defined dichotomously (unilateral vs bilateral). We assessed whether there is stepwise increased risk of pulmonary complications among patients without, with unilateral, and with bilateral pulmonary contusion. Methods: We identified adults admitted with rib fractures using the largest US inpatient database. After propensity-score-matching patients without vs with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
7
1
4
Order By: Relevance
“…There has been some debate as to whether lung contusions increase ICU LOS. Multiple studies [ 7 , 35 , 36 ] have reported that lung contusions were associated with worse outcomes and prolonged ICU and hospital LOS. Fokin et al and Dhar et al did not find differences in ICU LOS with or without lung contusions in major trauma patients [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been some debate as to whether lung contusions increase ICU LOS. Multiple studies [ 7 , 35 , 36 ] have reported that lung contusions were associated with worse outcomes and prolonged ICU and hospital LOS. Fokin et al and Dhar et al did not find differences in ICU LOS with or without lung contusions in major trauma patients [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Because pulmonary contusions can vary in size and severity, dichotomously classifying the presence or absence of pulmonary contusions is insufficient to appreciate the extent of the injury. 14 Furthermore, the severity of the pulmonary contusions detected on CT scan can change radiographically over time, especially in the first hours after injury. 15,16 Surgical stabilization of rib fractures (SSRFs) is increasingly used in the management of patients with severe rib fractures.…”
mentioning
confidence: 99%
“…Currently, chest computed tomography (CT) is the recommended diagnostic modality, since it is highly sensitive in diagnosing pulmonary contusions 12,13 . Because pulmonary contusions can vary in size and severity, dichotomously classifying the presence or absence of pulmonary contusions is insufficient to appreciate the extent of the injury 14 . Furthermore, the severity of the pulmonary contusions detected on CT scan can change radiographically over time, especially in the first hours after injury 15,16 …”
mentioning
confidence: 99%
“…P ulmonary contusions are present in nearly 20% of adults hospitalized with multiple rib fractures. 1 Inflammatory sequelae of pulmonary contusions can reduce thoracic compliance 2,3 and potentiate acute respiratory distress syndrome or other respiratory morbidities. [4][5][6] Pulmonary contusion is a pathology existing along a spectrum of severity, yet many databases, ontologies, and studies binarily classify contusions as present or absent.…”
mentioning
confidence: 99%